Microemulsion and Sol-Gel Synthesized ZrO2-MgO Catalysts for the Liquid-Phase Dehydration of Xylose to Furfural - Almudena Parejas (Molecules, 2017)
Two series of catalysts were prepared by sol-gel and microemulsion synthetic procedure (SG and ME, respectively). Each series includes both pure Mg and Zr solids as well as Mg-Zr mixed solids with 25%, 50% and 75% nominal Zr content. The whole set of catalysts was characterized from thermal, structural and surface chemical points of view and subsequently applied to the liquid-phase xylose dehydration to furfural. Reactions were carried out in either a high-pressure autoclave or in an atmospheric pressure multi-reactor under a biphasic (organic/water) reaction mixture. Butan-2-ol and toluene were essayed as organic solvents. Catalysts prepared by microemulsion retained part of the surfactant used in the synthetic procedure, mainly associated with the Zr part of the solid. The MgZr-SG solid presented the highest surface acidity while the Mg3Zr-SG one exhibited the highest surface basicity among mixed systems. Xylose dehydration in the high-pressure system and with toluene/water solvent mixture led to the highest furfural yield. Moreover, the yield of furfural increases with the Zr content of the catalyst. Therefore, the catalysts constituted of pure ZrO2 (especially Zr-SG) are the most suitable to carry out the process under study although MgZr mixed solids could be also suitable for overall processes with additional reaction steps.